Pengaruh Kepemimpinan Transformasional Kepala Sekolah, Budaya Organisasi, Lingkungan Kerja terhadap Performance Guru SD Negeri di Kecamatan Labuan Amas Utara Kabupaten Hulu Sungai Tengah - Siti Zainab Muthia Ulfah; Ahmad Suriansyah; Sulistiyana Sulistiyana (LP. Ma'arif Janggan Magetan, 2024)
This research aims to describe and analyze the influence of the Principal's Transformational Leadership, Organizational Culture, Work Environment on the Performance of Public Elementary School Teachers in North Labuan Amas District, Hulu Sungai Tengah Regency. The research method uses a quantitative approach, correlational research design uses cross sectional techniques. The research population was 214 teachers from 28 elementary schools in LAU sub-district and 140 respondents were taken as research samples using proportional random sampling techniques. The data collection instrument is a questionnaire that has been tested for validity and reliability. The results of data collection were analyzed using SPSS Version 25. Data analysis took the form of descriptive analysis, classical assumption testing, hypothesis testing using path analysis with the multiple regression method, and the Soebel test. The results of the analysis of the regression coefficient values ​​of the principal's transformational leadership variable on teacher performance were 0.368, the organizational culture variable on teacher performance was 0.308, the work environment variable on teacher performance was 0.251, the principal's transformational leadership variable on organizational culture was 0.629, the work environment variable on culture organization is 0.237, the principal's transformational leadership variable on teacher performance through organizational culture is 0.046 and the work environment variable on teacher performance through organizational culture is 0.022. The conclusion of this research is that the principal's transformational leadership, organizational culture, work environment and teacher performance are in the high category. There is a partial direct influence between the principal's transformational leadership, organizational culture, work environment and elementary school teacher performance in LAU District. There is an indirect influence between the principal's transformational leadership on teacher performance through organizational culture and the work environment of SDN in LAU sub-district